Assessment of trends in the development of housing construction in the Republic of Kazakhstan - Mekebayeva, Zh.; Mekebay, N.; Yelshibayeva, A.; Kylbayev, Ye. (BUKETOV BUSINESS REVIEW, 2023)
Object: to identify and evaluate the main trends in the development of housing construction in the Republic of Kazakhstan. The article considers the development of the construction industry in modern economic and investment conditions. The growth trend in the field of construction organizations, the concept of achieving competitive advantages of construction firms were shown. Methods: based on specific statistical data, the main trends in this area were identified, correlation-regression analysis was carried out, and conclusions were drawn based on the results of the study. After drawing the trend line, forecasts were made for the following years. The accuracy of the forecast was checked. Findings: based on the identified trends, factors contributing to the sustainable development of housing were identified, their analysis and forecast were carried out. The development of housing construction in the Republic of Kazakhstan is mathematically justified and evaluated. The dynamics of the identified factors made it possible to systematize research and identify factors that have a positive impact on the sustainable development of housing construction. The volume of construction works, the index of physical volume, and the number of construction organizations are increasing. Conclusions: an analysis of the contribution of the construction sector to the economy of Kazakhstan in gross domestic product was carried out. The trend of development of the volume of construction works was evaluated. Factors affecting the volume of construction work were also selected. The trend of increasing the volume of housing commissioned in the Republic of Kazakhstan has been identified. The determination of the place of the construction industry in the economy and its role in public production was determined by the impact of the final results of its functioning on the economic and social development of the region.